2014
DOI: 10.4321/s1135-57272014000600012
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis crónicas virales B y C en población inmigrante en España

Abstract: the prevalences of hepatitis B and C virus infections in the immigrant population suggest they could have a substantial public health impact in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Based on these data, it is estimated that migrants from endemic countries account for almost 40% of all chronic HBV infected cases in Spain ( 10 ). One study found that in Spain, African migrants accounted for the highest proportion of HBV prevalence in the population ( 11 ). In addition, late presentation to viral hepatitis specialist care is frequent in Spain and 35% of HBV patients who present late to care are foreign-born ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data, it is estimated that migrants from endemic countries account for almost 40% of all chronic HBV infected cases in Spain ( 10 ). One study found that in Spain, African migrants accounted for the highest proportion of HBV prevalence in the population ( 11 ). In addition, late presentation to viral hepatitis specialist care is frequent in Spain and 35% of HBV patients who present late to care are foreign-born ( 12 ).…”
Section: Introductionmentioning
confidence: 99%